Analisis Rasio Likuiditas Dan Rasio Solvabilitas Dalam Mengukur Kinerja Keuangan PT. Kawasan Industri Makassar - Anita Paulisa; Renny Mointi; Monalisa Monalisa (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
Analysis of Liquidity Ratios and Solvency Ratios in Measuring Financial Performance PT. Kawasan Industri Makassar (Persero), Thesis Management Study Program Sekolah Tinggi Ilmu Manajemen Lembaga Pendidikan Indonesia (STIM-LPI) Makassar. (supervised by Renny Mointi, S.E., M.M and Monalisa, S.E., M.M). This research aims to determine the Liquidity Ratio and Solvency Ratio in Assessing the Financial Performance of PT. Kawasan Industri Makassar (Persero). The type of research used in the research is quantitative. The data processed is the financial report of PT. Kawasan Industri Makassar (Persero) 2019-2021 which consists of the balance sheet. Research results from the liquidity ratio measured using the current ratio show that the financial performance of PT. KIMA is said to be less than reasonable and safe because it is below the industry average standard. On the quick ratio of financial performance. PT. KIMA Makassar is said to be good/reasonable and safe because it is above the industry standard from 2019 to 2021, namely 296%, 304% and 159% for the industry standard of 150%. The Solvency Ratio with Debt to Total Asset Ratio from 2019 and 2020 to financial performance is good/safe, whereas in 2021 it is said to be less good because it is above the industry average standard, namely 38%, with the industry standard being <35%. In the Debt to Total Equity Ratio, 2019 to 2020 is good/safe regarding financial performance because it is below the industry average set at 47%, 26% and 61%, while the good industry standard is <80%.